A relação entre escolarização pública e o contexto da Escola do campo: Um estudo de caso no município de Boa Vista/PB - Meira, Iranete de Araújo (2013)
The present research was carried out in a countryside public school, located in the town of Boa Vista, state of Paraíba. Its concern was to think about a Popular Rural Public School, by means of analyzing the impact of this proposal in the schooling process of the local context. From that, the possibility of dialoguing with education situated in rural areas of the referred town was considered. With this, the study aimed at understanding how the school José Pereira de Oliveira relates to the proposal of Rural Education. The theoretical framework which guided the research emerged from the context of popular education with emphasis on rural education, based on Freire (1996) Brandão (1984, 1983, 2002 and 2005), Vale (2001), Beisegel (2008), Paiva (1986); also, the specific field of Rural education is based on Caldart (2004, 2009), Fernandes & Jesus (2004), Kings (2011), and Arroyo (2007 and 2010). The discussions of this work also attempt to enhance and socialize popular knowledge derived from the collective memory and the everydayness of life with school knowledge, in an attempt to contribute to the achievement of a popular rural public education proposal. The methodology was based on a case study conducted by Flick (2004); on the universe of the description of semi-structured oral interviews as discussed in Chizzoti (2008); on Richardson (1996) and Gatti (2007); the official documents regarding rural education specific legislation (BRAZIL / MEC 2002, 2004 and 2010) were also analyzed. From the perspective of understanding the categories of analysis: Public Schooling, Rural area and teacher training, units of "record" and "analysis" through Franco (2008) and Bardin (1997) as a constituent of the fabric of the context of the local education were used as references. From these, remnants of a policy of rural education and traditional elements that travel in search of the conquest of a rural education proposal were found.